Remarks on G-Metric Spaces. (16th January 2013) - Samet, Bessem; Vetro, Calogero; Vetro, Francesca
Abstract : In 2005, Mustafa and Sims (2006) introduced and studied a new class of generalized metric spaces, which are called G -metric spaces, as a generalization of metric spaces. We establish some useful propositions to show that many fixed point theorems on (nonsymmetric) G -metric spaces given recently by many authors follow directly from well-known theorems on metric spaces. Our technique can be easily extended to other results as shown in application.